A Cognitive Model of the Antecedents and Consequences of Satisfaction Decisions - Oliver, Richard L. (Journal of Marketing Research, 1980)
A model is proposed which expresses consumer satisfaction as a function of expectation and expectancy disconfirmation. Satisfaction, in turn, is believed to influence attitude change and purchase intention. Results from a two-stage field study support the scheme for consumers and nonconsumers of a flu inoculation.